Algorithms, Filter Bubbles, and Information Consumption Patterns: Implications of Mass Communication In Digital Platforms - Yuhelna, Yuhelna; Huwaidah, Wulan Ariqah; Novia, Novia; Ardila, Ardila; Rahmat, Karel Gusmin; Mulyadi, Akbar (Journal of Humanity Studies, 2024)
The development of digital technology and algorithms used by social media platforms has transformed the patterns of information consumption in society. The phenomenon of the filter bubble, where users are exposed only to information that aligns with their preferences and beliefs, has narrowed the space for public discourse. This study aims to explore the impact of algorithms on mass communication and its implications for information consumption patterns. The research utilizes a literature review with a descriptive qualitative approach, analyzing various articles and studies related to the influence of algorithms and the filter bubble on media interactions and audiences. The findings reveal that algorithms play a significant role in directing and limiting the types of information users are exposed to. This reinforces the formation of echo chambers, where individuals are more likely to receive information that confirms their existing beliefs, reducing the diversity of perspectives. The study also finds that this phenomenon may exacerbate social polarization, shrink the space for constructive dialogue, and influence political and social behavior. As a result, mass communication in the digital era faces new challenges in creating an inclusive and open public space. This research is expected to provide insights for the development of media policies and digital literacy to address the evolving landscape of mass communication in the future.